Salud y seguridad ocupacional en trabajadores agrícolas del centro experimental Salache-UTC. - Escudero Fajardo, Juan Fernando (2021)
This work emphasizes improving occupational health and safety (OSH) conditions in agricultural personnel and identifying and evaluating occupational hazards for their control and mitigation. This research aimed to develop a control and mitigation plan for occupational risks for the workers in "Salache Bajo" Eloy Alfaro Parish. In Salache "CEASA" Academic Experimental Center of the Technical University of Cotopaxi, the workers are exposed to occupational risks during their working hours. According to their work area, they were identified through a site visit to establish a flow diagram according to work areas and responsibilities. It was proceeded to fill in the Identification, Qualitative Estimation and Risk Control matrix, arranged by IESS (Ecuadorian Social Security Institute), thus obtaining a broad panorama of the current situation in which they find our place of study. Then, compliance with regulations on OSH (Occupational Health and Safety) was inspected based on the inspection list (Checklist) of the IESS (Ecuadorian Institute of Social Security) 1-A-9 workers to determine compliance with mandatory regulations in SST / Ecuador insurance. Finally, we proceeded to generate a work risk mitigation and control plan with the information obtained, focusing on the shortcomings that were diagnosed using current national and international regulations, thus systematizing them in a final document.